Food Additives and Food Preservatives for Domestic and Industrial Food Applications - Awuchi, Chinaza Godswill; Twinomuhwezi, Hannington; Igwe, Victory Somtochukwu; Amagwula, Ikechukwu Otuosorochi (Journal of Animal Health, 2020)
Purpose: The study focused on food additives and preservatives, their health and nutritional benefits, and their types and safety regulations, including flavourants. Food additives are substances which are added to food to preserve its flavor or enhance its appearance, taste, or other qualities. Methodology: The systematic review evaluated the current updates and development in food additives and their applications in food industries and homes. Findings: The food additives currently in use are added to food as emulsifiers, colorants, flavorants, nutrients, or preservatives. Preservatives inhibit the growth of yeasts, bacteria, and molds in foods. Food additives can be directly (intentional) or indirectly (unintentional) added. Foods may contain some residues of chemicals used during production of animal or plant crops, including growth hormones, pesticides, antibiotics, etc. The use of most food additives is visibly beneficial as it results in improved the public health and the prevention of spoilage, which enhances food supply. However, there is controversy over the use of some common food additives. This is partly due to some individuals are hypersensitive and suffer allergic reactions if they are exposed to some of these chemical additives. Additionally, some individuals hold the belief that low levels of chronic toxicities and diseases might be caused in larger population by exposures to some of these chemical substances. There are many thousand food additives currently in use, all of which are designed to do specific function in making food safer, more nutritious, more appealing, or last longer. Contribution to theory, practice, and policy: The study provides thorough and concise information on the major food additives that are currently used at home and food industries to preserve food flavor or enhance its appearance, taste, or other qualities.